Lanreotide Autogel in the Treatment of Persistent Diarrhea following a Total Colectomy - Patrick Schoeters; Karl De Pooter (Case Reports in Gastrointestinal Medicine)
Diarrhea is one of the most common complications following colectomy in patients with slow transit constipation (STC). Early postoperative diarrhea is usually treated with opioid agonists; however, to date, published data on the management of persistent diarrhea after colectomy for STC are scarce. Here, we report a case of severe diarrhea after a total colectomy with ileorectal anastomosis. One year after the surgery, the patient presented with persistent diarrhea. Treatment with a long-acting somatostatin analogue, lanreotide Autogel, was initiated. One month after the first injection of lanreotide Autogel the diarrhea was resolved. The patient’s stool transit was markedly improved (type 4 or type 5 according to the Bristol Stool Chart compared to type 7 before the treatment), positively affecting the patient’s quality of life (mean score of 2.1 on the Irritable Bowel Syndrome Quality of Life questionnaire compared to 3.9 before the treatment). This case report describes a successful use of lanreotide Autogel in a patient with persistent diarrhea after a total colectomy.